2015
DOI: 10.3758/s13421-015-0583-6
|View full text |Cite
|
Sign up to set email alerts
|

Late L2ers can acquire grammatical features that do not occur in their L1: Evidence from the effect of animacy on verb agreement in L1 Chinese

Abstract: Second language (L2) learners often have persistent difficulty with agreement between the number of the subject and the number of the verb. This study tested whether deviant L2 verb number agreement reflects maturational constraints on acquiring new grammatical features or resource limitations that impede access to the representations of L2 grammatical features. L1-Chinese undergraduate students at three age of arrival (AoA) levels were tested for online verb agreement accuracy by completing preambles in three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…For instance, Alemán Bañon et al (2014) showed that L1 English speakers can display P600 effects when processing gender agreement violations in L2 Spanish. Similar results have been reported in studies with German–Italian bilinguals ( Rossi et al, 2006 ), Spanish–English bilinguals ( Kotz et al, 2008 ), and English–French bilinguals ( Foucart and Frenck-Mestre, 2012 ). In a recent MEG study, Bastarrika and Davidson (2017) showed that L1 Spanish speakers can learn syntactic rules of Basque which are not present in Spanish and process them like native speakers of Basque.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…For instance, Alemán Bañon et al (2014) showed that L1 English speakers can display P600 effects when processing gender agreement violations in L2 Spanish. Similar results have been reported in studies with German–Italian bilinguals ( Rossi et al, 2006 ), Spanish–English bilinguals ( Kotz et al, 2008 ), and English–French bilinguals ( Foucart and Frenck-Mestre, 2012 ). In a recent MEG study, Bastarrika and Davidson (2017) showed that L1 Spanish speakers can learn syntactic rules of Basque which are not present in Spanish and process them like native speakers of Basque.…”
Section: Introductionsupporting
confidence: 89%
“…Some other studies observed a reduction or an absence of the P600 in non-native syntactic processing, suggesting that violations on L2 grammatical structures are not salient enough when those structures cannot been transferred from L1 ( Ojima et al, 2005 ; Chen et al, 2007 ; Sabourin and Stowe, 2008 ; Foucart and Frenck-Mestre, 2011 ; Zawiszewski et al, 2011 ). Interestingly, studies where different proficiencies of bilinguals are compared showed a change from N400 (for low proficient bilinguals) to P600 (for high proficient bilinguals), revealing the learning process of the L2 ( Osterhout et al, 2006 ; McLaughlin et al, 2010 ; Foucart and Frenck-Mestre, 2012 ; White et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Electrophysiologic evidence suggests naïve learners acquiring grammatical information in a statistical learning format can achieve high behavioral accuracy while still showing physiologic responses that differ from native language users (Mueller et al, 2009; Foucart and Frenck-Mestre, 2012). Consistent with the idea that the early neural network is not yet stable, transitional physiological responses have been reported in a study that involved gender class learning (Foucart and Frenck-Mestre, 2012). We propose that the dynamic shifts in level and location of activation in the learning network, as well as correlations with behavior, represent physiologic attempts (successful or otherwise) to optimize the learning network.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of influence of the L1 during online L2 morphosyntactic processing has been demonstrated in eye-tracking (Frenck-Mestre and Pynte, 1997) and ERP studies (e.g., Sabourin, 2003; Ojima et al, 2005; Tokowicz and MacWhinney, 2005; Kasparian et al, 2010; Foucart and Frenck-Mestre, 2011, 2012; White et al, 2012). Research has also examined the factors at play in modulating the degree of L1–L2 influence – linguistic similarity, L2 proficiency and exposure levels have been shown to affect the extent of L1-transfer and the degree of native-like-ness in the L2 (see reviews by Kotz, 2009 and Caffarra et al, 2015).…”
Section: Introductionmentioning
confidence: 99%